FORMATION OF TEACHER’S PROFESSIONAL COMPETENCE AS ONE OF THE CONDITIONS OF A SUCCESSFUL PREVENTIVE ORGANIZATION ACTIVITIES WITH DEVIANT ADOLESCENTS - Kulinka Ю.С. (Pedagogy of Higher and Secondary Education, 2022)
The article depicts the essence of professional competency of the future teachers as one of the conditions oа successful organization of preventive activity with deviation teenagers, the analysis of psycolo-pedagogical literature of notion’s substance "competency" and "competence" is presented, also here is the model of competent activity of the teacher in preventive education of growing generations.